COMMUNITY OF ASSESSMENT PRACTICE OR INTERESTS: THE CASE OF EAP WRITING ASSESSMENT - Al-Maamari, Faisal (Universitas Pendidikan Indonesia, 2016)
Setting, disseminating and applying assessment standards are part of university academic programmes of study. Nowadays, assessment is increasingly viewed from a social practice perspective, and so doing entails exploring how the quality of assessment is shaped by interaction and co-participation with different communities of practice. Therefore, based on this perspective, the study reported here aimed to examine the assessment policies and practices of laboratory report writing of first year students in credit-bearing, English for Special Purposes programmes at a university in the Sultanate of Oman. Interviews of programme administrators and the instructors plus institutional and programme documents were examined to investigate these assessment policies and practices. The programme administrators were asked about how they planned the written assessment in their programmes, and the instructors were asked about their experiences of these assessments. The data were then analysed thematically using community of practice framework, namely in relation to (1) a shared repertoire of communal resources, (2) mutual engagement, and (3) a sense of joint enterprise. It was found that instead of community of practice, there were (sub)communities of practices wherein interaction, negotiation and communication amongst members and non-members were punctuated by control, power and autonomy, all working with the aim of narrowing the range between the personal goals of the academic and the communal goals of the institution. The overarching conclusion is that in their assessment practices, the two instructional programmes exhibited varying degrees of community of practice based on the above three attributes.